Factors of students’ non-lecture attendance and administrative strategies for its effective management in Nigerian universities - Nwamaka, Osakwe Grace; Vinella, Okonta (International Journal of Evaluation and Research in Education (IJERE), 2025)
The aim of the study was to investigate factors of students’ non lecture attendance and administrative strategies used with a view to ascertain the extent of its implementation in universities in South-South states in Nigeria. A population of 22 universities from which a sample of six was drawn and 350 respondents; 50 lecturers and 300 students formed the sample size. The study was guided by three research questions and adopted the descriptive survey research design. A questionnaire was the instrument used for the study. It was divided into four subsections, which is part A, B, C and D. Its face and content validity were determined through expert judgment while the reliability index was determined using Cronbach alpha. Descriptive statistics was used to analyze the data collected. The findings revealed that emotional problems (3.93), sickness (3.71), finance (3.48), lecturers teaching skills (3.21) were key factors of non-lecture attendance. The main administrative strategies used were 75% policy on lecture attendance (3.33), administering short and unannounced quiz (3.24), provision of comfortable classrooms (3.30); while the strategies were sometimes used. The recommendations include counseling students and a 100% implementation of any policy adopted by individual universities.